Minipool testing for SARS‐CoV‐2 RNA in United States blood donors. Issue 8 (27th May 2021) - Bakkour, Sonia; Saá, Paula; Groves, Jamel A.; Montalvo, Leilani; Di Germanio, Clara; Best, Sonja M.; Grebe, Eduard; Livezey, Kristin; Linnen, Jeffrey M.; Strauss, Donna; Kessler, Debra; Bonn, Mark; et al.
Abstract: Background: SARS‐CoV‐2 RNA prevalence in blood donors from large geographic areas of high community transmission is limited. We tested residual donor plasma minipools (MPs) to determine SARS‐CoV‐2 RNAemia prevalence in six United States areas. Study Design/Methods: Blood donations collected from 7 March 2020 to 25 September 2020 were tested for SARS‐CoV‐2 RNA (vRNA) in MP of 6 or 16 donations using the Grifols Procleix SARS‐CoV‐2 research‐use only (RUO) transcription‐mediated amplification (TMA) assay. Reactive results were confirmed using an alternate target region TMA assay. Reactive MPs were tested by TMA after serial dilution to estimate viral load. Testing for anti‐SARS‐CoV‐2 antibodies and infectivity was performed. Results: A total of 17, 995 MPs corresponding to approximately 258, 000 donations were tested for vRNA. Three confirmed reactive MP16 were identified. The estimated prevalence of vRNA reactive donations was 1.16/100, 000 (95% CI 0.40, 3.42). The vRNA‐reactive samples were non‐reactive for antibody, and the estimated viral loads of the (presumed single) positive donations within each MP ranged from <1000 to <4000 copies/ml. When tested, no infectivity was observed in inoculated permissive cell cultures. Discussion: Blood donation MP‐nucleic acid testing (NAT) indicated that SARS‐CoV‐2 RNAemia is infrequent and, when detected, the vRNA was at low concentrations. Only one RNA‐reactive MP could be tested for infectivity for operational reasons and was not infectious in cell culture. These findings support current recommendations from international and national regulatory agencies to not screen donors by NAT.